Role Perception of Village Panchayat Pradhan in Manipur - A.Tarajit. Singh , D.K. Bose and R.K. Imotomba, (Indian Journal of Extension Education, 2016)
The study was conducted in 9 C.D. Blocks in the districts of Manipur in village region. Majority of the respondentsbelongs to young middle age group also the respondents had 'medium' level of socio-economic status. Dimension wiserole perception results pointed that 87% of respodents' perception of roles was high to medium in case of dimension ofgeneral role. Respondents have perceived medium level of role perception in agriculture, education, welfare and otherrelated activities. As regards overall role perception of village Panchayat Pradhan majority (59.74%) of respondents hadmedium to low perception of roles. It was inferred that relationship between independent variables i.eEducation, Annualincome, Mass media exposure, Leadership preference and Achievement motivation had positive and significant effect onrole perception of Village Panchayat Pradhan.